(untitled) (Revista Lusófona de Educação, 2016)
The current educational context entails new challenges and opportunities for educators and students. Among these are found the Information and Communication Technology tools (ICTs). They bring new paradigms to educational dynamics, as is the case of Digital Educational Books (DEB). Consequently, this study intends to access the perception of the user’s experience (UX) in a group of teachers using the WEBMAT® educational platform. The data collected is based on the exploitation of a high-fidelity prototype, making it possible to evaluate how the principles of Design Interaction, applied to the development of DEB, provide support to the teachers in understanding and creating tasks. This study has provided data that is intended as a contribution towards improving the quality of these educational platforms as well as assisting educators in developing educational tasks.